The Life of a Jazz Festival During a Pandemic - Cancura, Petr (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Programming Manager Petr Cancura describes the impact of the COVID-19 pandemic on the Ottawa Jazz Festival.